Preliminary investigation into the differences in vocalisations between wild saki monkeys (Pithecia spp.) - Muir, Jen; Barnett, Adrian A.; Svensson, Magdalena S. (Neotropical Primates, 2021)
Information on primate vocalisations can be applied in several ways, including: improving captive welfare, as a census tool for cryptic species, or to investigate the impacts of anthropogenic disturbance on species’ behaviour (Delgado and van Shaik, 2000; Konrad and Geissman, 2006; Jacobsen et al., 2010). Vocalisations can be used as a taxonomic tool, and structural differences between calls have been used to compare a wide variety of taxa, including species of gibbon (Hylobatidae spp., Ruppell, 2010), marmosets (Callithrix spp., Mendes et al., 2009), owls (Strigidae spp., Flint et al., 2015), wolves (Canis spp., Kershenbaum et al., 2016), and galagos (Galagidae spp., Svensson et al., 2017). Additionally, differences in voca- lisations across taxonomic groups can be used to help determine genetic distances between species or investigate why vocal behaviours evolved (Blumstein and Armitage, 1998; Ord and Garcia-Porta, 2012).